2016
DOI: 10.1002/uog.15815
|View full text |Cite
|
Sign up to set email alerts
|

Mean arterial pressure at 12, 22, 32 and 36 weeks' gestation in screening for pre-eclampsia

Abstract: Objective To examine the distribution of mean arterial pressure (MAP) at 12, 22,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…For all these predictors, the performance was better for early than for late PE, and was better when assessed later in pregnancy than at 11–13 weeks, i.e. closer to the development of PE.…”
Section: Combined Screening Strategiesmentioning
confidence: 96%
See 1 more Smart Citation
“…For all these predictors, the performance was better for early than for late PE, and was better when assessed later in pregnancy than at 11–13 weeks, i.e. closer to the development of PE.…”
Section: Combined Screening Strategiesmentioning
confidence: 96%
“…Combined screening has been the subject of approximately 400 PubMed articles up to April 2018. Multiple studies have shown that women who go on to develop PE have, on average, higher mean arterial pressure, higher concentrations of maternal serum soluble fms‐like tyrosine kinase‐1 (sFlt‐1) and alpha‐fetoprotein (AFP), and lower concentrations of pregnancy‐associated plasma protein‐A (PAPP‐A) and PlGF, along with higher resistance in the uterine arteries, compared with women who do not. For all these predictors, the performance was better for early than for late PE, and was better when assessed later in pregnancy than at 11–13 weeks, i.e.…”
Section: Combined Screening Strategiesmentioning
confidence: 99%
“…Mean arterial pressure (MAP), a biophysical marker is known to be a better predictor for screening preeclampsia [15] [16]. It represents average pressure in a patient's arteries during one cardiac cycle and is considered as a better indica-…”
Section: Introductionmentioning
confidence: 99%
“…Second, many potential biomarkers have been extensively investigated and it has been established that, at present, useful biomarkers for the prediction of PE are: uterine artery pulsatility index (UtA‐PI), mean arterial pressure (MAP) and serum placental growth factor (PlGF) measured at 11–13 and 19–24 weeks' gestation; UtA‐PI, MAP, PlGF and serum soluble fms‐like tyrosine kinase‐1 (sFlt‐1) measured in the early third trimester; and MAP, PlGF and sFlt‐1 evaluated in the late third trimester. The methodology for obtaining appropriate measurements of biomarkers and auditing of results has also been established.…”
mentioning
confidence: 99%
“…Consequently, appropriate evaluation and application of biomarkers in screening requires prior standardization by expressing the measured values as multiples of the median (MoM). In pregnancies that develop PE, MoM values of MAP, UtA‐PI and sFlt‐1 tend to be higher and PlGF tends to be lower than in normal pregnancies; the effect size increases with increasing severity of the disease, quantified by the gestational age at delivery.…”
mentioning
confidence: 99%